2010
DOI: 10.1007/s12224-010-9081-6
|View full text |Cite
|
Sign up to set email alerts
|

Host Dependence and Preference of the Root Hemiparasite, Pedicularis cephalantha Franch. (Orobanchaceae)

Abstract: The interaction between parasitic plants and their hosts is an important topic in both agriculture and ecology. Little, however, is known about that of the hemiparasite Pedicularis. It is essential to understand the host dependence and preference of Pedicularis for successful cultivation of plants in this genus and for understanding the roles they play in natural communities. We tested the effects of two herbaceous host species (Trifolium repens and Polypogon monspeliensis) on the survival and growth performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 45 publications
0
17
2
Order By: Relevance
“…Higher concentration levels of mineral ions (e.g., potassium) along with lower water potentials facilitate nutrient absorption by parasitic plants from their host (Westwood 2013). Virtually, all root hemiparasitic plants benefit greatly from attachment to a suitable host plant (Loveys and Tyerman 2002;Matthies 1997;Ren et al 2010). As most root hemiparasites extract nutrients directly from host roots, changes in resource allocation to host roots may have a significant effect on growth of the root hemiparasites.…”
Section: Introductionmentioning
confidence: 99%
“…Higher concentration levels of mineral ions (e.g., potassium) along with lower water potentials facilitate nutrient absorption by parasitic plants from their host (Westwood 2013). Virtually, all root hemiparasitic plants benefit greatly from attachment to a suitable host plant (Loveys and Tyerman 2002;Matthies 1997;Ren et al 2010). As most root hemiparasites extract nutrients directly from host roots, changes in resource allocation to host roots may have a significant effect on growth of the root hemiparasites.…”
Section: Introductionmentioning
confidence: 99%
“…For example, species of Euphrasia parasitize both monocot (Poaceae) and eudicot (Fabaceae) plants (Yeo, 1964). In contrast, some cases of high host specificity have also been documented (Ren et al, 2010). Studies carried out to evaluate the possibility of establishing some parasitic species of Euphrasia (Yeo, 1961;1964) under culture conditions found that the plants can grow when planted as seeds or seedlings in pots in which a host has previously been established.…”
Section: Introductionmentioning
confidence: 99%
“…First, as a hemiparasitic plant it may decrease the host plant's fitness by reducing the available resources for growth and reproduction (Marvier, 1996;Salonen and Lammi, 2001;Jiang et al, 2003;Lehtonen et al, 2005;Yoder et al, 2009;Hautier et al, 2010;Ren et al, 2010aRen et al, ,2010bSui et al, 2014;Bao et al, 2015). Second, it can release root exudates that have allelopathic effects on the seed germination and seedling growth of neighboring Pooideae grasses (Wei, 2010;Bao and Wang, 2011;Shang and Xu, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Plant growth in the area is limited by two main factors related to the climate: low temperatures and short growing season (Ren et al, 2010a(Ren et al, ,2010bLi et al, 2013). Annual temperature and precipitation range from À1.37e5.5 C and 270e520 mm, respectively, and winter frost continues for 7 months from Oct. to May each year.…”
Section: Introductionmentioning
confidence: 99%